1992
DOI: 10.1172/jci115928
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycosylation endproducts block the antiproliferative effect of nitric oxide. Role in the vascular and renal complications of diabetes mellitus.

Abstract: Advanced glycosylation endproducts (AGEs) accumulate on long-lived tissue proteins such as basement membrane collagen and have been implicated in many of the long-term complications of diabetes mellitus. These products originate from glucose-derived Schiff base and Amadori products but undergo a series of complex rearrangement reactions to form ultimately protein-bound, fluorescent heterocycles. AGEs can react with and chemically inactivate nitric oxide (NO), a potent endothelial cell-derived vasodilator and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
2
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(85 citation statements)
references
References 32 publications
1
80
2
2
Order By: Relevance
“…This may relate in part to AGEs promoting stiffening of the aorta. Furthermore, AGEs in the vascular tissue may induce these deleterious vascular effects is by impairing nitric oxide synthase activity in endothelial cells as has been previously described [36,77,78]. As noted previously, AGEs are thought to activate the NF-κB pathway primarily as a result of their ligation with RAGE.…”
Section: Discussionmentioning
confidence: 73%
“…This may relate in part to AGEs promoting stiffening of the aorta. Furthermore, AGEs in the vascular tissue may induce these deleterious vascular effects is by impairing nitric oxide synthase activity in endothelial cells as has been previously described [36,77,78]. As noted previously, AGEs are thought to activate the NF-κB pathway primarily as a result of their ligation with RAGE.…”
Section: Discussionmentioning
confidence: 73%
“…By contrast, other recent studies show that AGEs quench NO although the mechanisms by which this occurs are yet to be elucidated. For example, Bucala's group [52,53] showed that experimental diabetes is associated with an impaired vasodilatory response to both endotheliumdependent (acetylcholine) and endothelium independent (nitroglycerine) agents, a finding which is consistent with AGE mediated inactivation of NO within the subendothelial space. It follows then, that if AGEs mediated the effects of diabetes on the NO system, diabetes would be associated with NO deficiency rather than an excess as postulated by Williamson et al [54].…”
Section: Discussionmentioning
confidence: 88%
“…Advanced glycation end products are viewed as quenching NO [14] and it is possible that the effect of PTB in attenuating the increase in blood pressure in the diabetic rats was related to reduced AGE accumulation leading to enhanced action of the vasodilator NO. By contrast, there seemed to be an unexplainable increase in blood pressure with PTB treatment in control rats.…”
Section: Discussionmentioning
confidence: 99%